Omeprazole Minimally Alters the Fecal Microbial Community in Six Cats: A Pilot Study - Schmid, Sarah M.; Suchodolski, Jan S.; Price, Josh M.; Tolbert, M. K. (Frontiers in Veterinary Science, 2018)
Although they have historically been thought of as safe medications, proton pump inhibitors such as omeprazole have been associated with an increased risk of enteric, particularly Clostridium difficile, infections in people. In cats, omeprazole is often the first choice acid suppressant prescribed for the treatment of upper gastrointestinal ulceration and bleeding. Despite this, no studies to date have explored the effect of omeprazole on the feline fecal microbiome and metabolome. Therefore, the purpose of this pilot study was to evaluate the effect of prolonged omeprazole administration on the fecal microbiome and metabolome in healthy cats in order to identify targets for analysis in a larger subset of cats with gastrointestinal disease. A within-subjects, before and after, pilot study was performed whereby six healthy adult cats received 60 days of placebo (250 mg lactose PO q12h) followed by 5 mg (0.83-1.6 mg/kg PO q12h) omeprazole. On days 0, 30, and 60 of placebo and omeprazole therapy, the fecal microbiome and metabolome were characterized utilizing 16S rRNA sequencing by Illumina and untargeted mass spectrometry-based methods, respectively. Omeprazole administration resulted in no significant changes in the global microbiome structure or richness. However, transient changes were noted in select bacterial groups with omeprazole administration resulting in an increased sequence percentage of Streptococcus, Lactobacillus, Clostridium, and Faecalibacterium spp. and a decreased sequence percentage of Bifidobacterium spp. Significance was lost for all of these bacterial groups after adjustment for multiple comparisons. The fecal concentration of O-acetylserine and aminomalonate decreased with omeprazole therapy, but significance was lost after adjustment for multiple comparisons. The results of this pilot study conclude that omeprazole has a mild and transient impact on the fecal microbiome and metabolome when orally administered to healthy cats for 60 days. Based on the findings of this pilot study, evaluation of the effect of omeprazole specifically on Streptococcus, Lactobacillus, Clostridium, Faecalibacterium, and Bifidobacterium spp. is warranted in cats with primary gastrointestinal disease.